2015
DOI: 10.5194/hess-19-857-2015
|View full text |Cite
|
Sign up to set email alerts
|

Calibration approaches for distributed hydrologic models in poorly gaged basins: implication for streamflow projections under climate change

Abstract: Abstract. This study tests the performance and uncertainty of calibration strategies for a spatially distributed hydrologic model in order to improve model simulation accuracy and understand prediction uncertainty at interior ungaged sites of a sparsely gaged watershed. The study is conducted using a distributed version of the HYMOD hydrologic model (HYMOD_DS) applied to the Kabul River basin. Several calibration experiments are conducted to understand the benefits and costs associated with different calibrati… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
62
0
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(77 citation statements)
references
References 79 publications
1
62
0
4
Order By: Relevance
“…Migliaccio and Chaubey (2007) recommend the use of SC technique for calibrating nested sub-basins with hydrologic connections. Contrary to the SC technique used by Wi et al (2015), Shrestha et al (2016) and Leta et al (2017), whereby the calibrated and optimized parameter set obtained in the upstream gauge is fixed while calibrating the downstream counterpart, that approach was not adopted in this study because of the hydrological connection between upstream and downstream hydrometric stations. Note that the same number of parameters and their ranges were used to initiate each calibration.…”
Section: Model Sensitivity Analysis Calibration Validation and Uncementioning
confidence: 99%
See 1 more Smart Citation
“…Migliaccio and Chaubey (2007) recommend the use of SC technique for calibrating nested sub-basins with hydrologic connections. Contrary to the SC technique used by Wi et al (2015), Shrestha et al (2016) and Leta et al (2017), whereby the calibrated and optimized parameter set obtained in the upstream gauge is fixed while calibrating the downstream counterpart, that approach was not adopted in this study because of the hydrological connection between upstream and downstream hydrometric stations. Note that the same number of parameters and their ranges were used to initiate each calibration.…”
Section: Model Sensitivity Analysis Calibration Validation and Uncementioning
confidence: 99%
“…However, calibration of CHMs to determine a suitable set of parameter values that can describe the hydrology of the catchment is not always an easy task . Studies have shown that the parameter set used to calibrate CHMs against flow measured only at the catchment outlet (single-site calibration (SSC)) may not produce similar results at other internal hydrometric stations within the catchment (Wang et al 2012;Wi et al 2015;Leta et al 2017). Furthermore, several researchers have demonstrated the effectiveness of calibrating CHMs with data from different parts of the catchment using simultaneous multi-site calibration (SMSC) over SSC (Wang et al 2012;Wi et al 2015;Chaibou Begou et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Shortcomings of this study also include the use of single streamflow gauge, as well as few rain gauges for ACRU model simulation. Model calibration and validation would have been more robust if several streamflow [50] and rainfall gauges were available, as the streamflows in the Bonsa catchment are more variable at the subcatchment than at the catchment scale. The abovementioned uncertainties were minimized by using physically meaningful sensitivity analysis of the ACRU model parameters in a companion paper [37] for the Bonsa catchment.…”
Section: Dealing With Uncertainties In Land Use Change Impact Assessmmentioning
confidence: 99%
“…The UIB is located within the geographical range of [31][32][33][34][35][36][37] ‱ N and 72-82 ‱ E, covering an area of 162,393 km 2 up to the Besham Qila gauging site (Figure 1). The basin hosts three gigantic massifs-western Himalaya at lower latitudes of the basin, Karakoram Range in further north (Trans-Himalayas), and Hindu Kush Range in the west of Karakoram-Himalaya ranges.…”
Section: Study Areamentioning
confidence: 99%